2016
DOI: 10.1021/acs.nanolett.6b00820
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase Embedded in Nanocarrier PEG Shell for Enhanced Tumor Penetration and Highly Efficient Antitumor Efficacy

Abstract: One of the major challenges in applying nanomedicines to cancer therapy is their low interstitial diffusion in solid tumors. Although the modification of nanocarrier surfaces with enzymes that degrade extracellular matrix is a promising strategy to improve nanocarrier diffusion in tumors, it remains challenging to apply this strategy in vivo via systemic administration of nanocarriers due to biological barriers, such as reduced blood circulation time of enzyme-modified nanocarriers, loss of enzyme function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(189 citation statements)
references
References 35 publications
(64 reference statements)
2
182
0
1
Order By: Relevance
“…Inspired by the findings, recombinant human HAase PH20 was conjugated on the surface of poly (lactic-co-glycolic acid) (PLGA) NPs to modulate ECM. The study revealed that PH20 conjugated NPs treatment achieved significantly improved distribution of NPs in 4T1 breast cancer xenograft mice due to ECM degradation and increased interstitial diffusion in solid tumors [148]. Interestingly, delivery of the NPs could also increase tumor vessel density, thereby increasing drug delivery efficacy and enhancing therapeutic effects [149].…”
Section: Nanoparticle-based Strategiesmentioning
confidence: 99%
“…Inspired by the findings, recombinant human HAase PH20 was conjugated on the surface of poly (lactic-co-glycolic acid) (PLGA) NPs to modulate ECM. The study revealed that PH20 conjugated NPs treatment achieved significantly improved distribution of NPs in 4T1 breast cancer xenograft mice due to ECM degradation and increased interstitial diffusion in solid tumors [148]. Interestingly, delivery of the NPs could also increase tumor vessel density, thereby increasing drug delivery efficacy and enhancing therapeutic effects [149].…”
Section: Nanoparticle-based Strategiesmentioning
confidence: 99%
“…However, HA that has been the systemically injected is subject to enzyme degradation while circulating and tends to induce muscle spasms and thromboembolism, as reported in clinical studies [47] . Very recently, Cheng et al demonstrated that the HA modification of drug-loaded NPs improved the efficacy of drug delivery by degrading the HA of the tumoral stroma [48] . In this study, rHuPH20 was employed to modify the surface of drugloaded poly(lactic-co-glycolic acid)-b-poly(ethylene glycol) NPs (PLGA-PEG-NPs).…”
Section: Overcoming Extracellular Barriers Using Nanomedicinementioning
confidence: 99%
“…At present, liposomes and polymeric nanoparticles are commonly used nanoparticle drug carriers and several of them have been approved by the US FDA for human use [9,10]. However, converting those nanoparticles into theranostic nanoparticles requires incorporation of imaging agents into the nanoparticles, such as radioactive, optical and MRI contrasts [6,[11][12][13]. Following administration, those nanoparticle drug carriers loaded with imaging agents can be broken-down in vivo and subsequently release contrast agents, resulting in different tissue distributions for the imaging contrasts and the drug carriers.…”
mentioning
confidence: 99%